Introducing biofortified rice and wheat through the public distribution system: An empirical analysis of its implications in Bihar and Odisha - Kumar, Anjani; Verma, Smriti; Saroj, Sunil; Kumar, Niraj (Indian Society of Agricultural Economics, 2021)
The paper examines the potential of India’s Public Distribution System for introducing biofortified crops to address the challenges of micronutrient deficiencies in Bihar and Odisha, two of the country’s most poverty-stricken states. The analysis indicate that the replacement by bio-fortified varieties had the potential to increase the intake of zinc and iron by nearly 33 per cent.